2008
DOI: 10.1111/j.1440-1681.2008.05005.x
|View full text |Cite
|
Sign up to set email alerts
|

Histamine‐induced Progression From Heterologous to Homologous Desensitization of Contraction in Smooth Muscle of Guinea‐pig Taenia Caeci

Abstract: 1. We have reported previously that, in the smooth muscle of guinea-pig taenia caeci, the development of carbachol-induced desensitization to carbachol and histamine has a similar time-course whereas desensitization to high K(+) is interrupted by sustained resensitization. 2. In the present study, we evaluated the development of histamine-induced desensitization to histamine, carbachol and high K(+) with respect to their regulation by resensitization, and compared it with carbachol-induced desensitization. 3. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…In the presence of extracellular Ca, carbachol‐induced desensitization to carbachol developed with interruption by an obscure phase of transient resensitization in its early stage in this smooth muscle. Such a peculiar phenomenon was also observed in agonist‐induced desensitization in smooth muscle of guinea pig taenia caeci 14,22–26 . as well as in human astrocytoma cells, 27 where calmodulin‐dependent protein kinase II and protein phosphatase 2B are thought to be involved in the early phase of desensitization and resensitization, respectively 27 .…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…In the presence of extracellular Ca, carbachol‐induced desensitization to carbachol developed with interruption by an obscure phase of transient resensitization in its early stage in this smooth muscle. Such a peculiar phenomenon was also observed in agonist‐induced desensitization in smooth muscle of guinea pig taenia caeci 14,22–26 . as well as in human astrocytoma cells, 27 where calmodulin‐dependent protein kinase II and protein phosphatase 2B are thought to be involved in the early phase of desensitization and resensitization, respectively 27 .…”
Section: Discussionmentioning
confidence: 72%
“…Such a peculiar phenomenon was also observed in agonist-induced desensitization in smooth muscle of guinea pig taenia caeci. 14,[22][23][24][25][26] as well as in human astrocytoma cells, 27 where calmodulin-dependent protein kinase II and protein phosphatase 2B are thought to be involved in the early phase of desensitization and resensitization, respectively. 27 It is possible that transient resensitization mechanisms are conserved widely among cells or tissues and play a significant role in modulating the initial process of desensitization for further regulation of cellular homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with our previousˆndings on Ca 2+ -dependent development of carbachol-induced heterologous desensitization in this smooth muscle. 8) In astrocytoma cells, we have found that Ca 2+ /calmodulin-mediated processes are involved in the initial process of histamine-induced desensitization to histamine. 14 15) It is possible that such Ca 2+ -dependent mechanisms are involved in the initial development of histamineinduced heterologous desensitization under normal physiological conditions.…”
Section: Histamine-induced Development Of Homologous Desensitization mentioning
confidence: 99%
“…Strips of taenia caeci were prepared from guinea pigs, weighing 250 400 g, as described previously. 8) The muscle strips were maintained in normal Locke-Ringer solution (normal solution), pH 7.8 at 30°C, with the following composition (mM): NaCl 154, KCl 5.6, CaCl 2 2.2, MgCl 2 2.1, NaHCO 3 6 and glucose 5.6. Contractions were induced cumulatively with histamine (10 -8 to 10 -4 M), carbachol (10 -9 to 10 -4 M) or isotonic K + -rich solution (high K + solution; 10 to 42 mM of K + ) at 30°C.…”
Section: Measurement Of Control Responsesmentioning
confidence: 99%